Pictures of the Shark : Stories - McNeely, Thomas H. (Book collections on Project MUSE., 2022)
"A sudden snowfall in Houston reveals family secrets. A trip to Universal Studios to snap a picture of the shark from Jaws becomes a battle of wills between father and son. A midnight seance and the ghost of Janis Joplin conjure the mysteries of sex. A young boy's pilgrimage to see Elvis Presley becomes a moment of transformation. A young woman discovers the responsibilities of talent and freedom. A mother finds peace with children in a hurricane. Pictures of the Shark, a novel in eight stories by award-winning Houston writer Thomas H. McNeely, moves from its main protagonist Buddy Turner's surreal world of childhood, into the wider worlds of sex, drinking, art, and ambition. Written over a period of twenty years, appearing in the country's finest literary journals, including Ploughshares, The Virginia Quarterly Review, Epoch, and Crazyhorse, shortlisted for the O. Henry Award, Best American Short Stories, and Pushcart Prize collections, the stories in Pictures of the Shark are gems that refract their characters' complex relationships. McNeely's characters - a faithless father tormented by his own infidelities, a hard-working mother who struggles with depression, a young woman finding her place in the world - will leap off the page and haunt your imagination"--